EFEKTIVITAS PENERAPAN METODE QUANTUM TEACHING PADA PENDEKATAN JELAJAH ALAM SEKITAR (JAS) BERBASIS KARAKTER DAN KONSERVASI - Sari, Yunita Kartika; Endang Susilowati, Sri Mulyani; Ridlo, Saiful (Journal of Biology Education, 2013)
This researchÂ  aimedÂ  measure the effectiveness of learning with Quantum Teaching methods in exploring environmentÂ  approach-based on characters and conservation to the activities and learning outcomes and character building of student at SMP N 1 Bae Kudus. Learning is effective if at least 80% in the classical KKM and liveliness of students achieving â¥ 75% of students showed an active response to the character of students attitudes and good. This type of research was quasi experimental research design using a pretest-posttest control group. The samples of this research were class VII F and VII G which determined by purposive random sampling. The independent variables include the application of Quantum Teaching Method JAS approach based on the character and conservation, while the dependent variable is the activity and student learning achievement.Â  Tests using the t test showed of average difference in pretest-posttest experimental class is larger than the class controls. The results of the analysis of test n-gain experimental learning activities grade students earned a higher average than the classical control class. Analysis of the character of students as measured by the attitude scale obtained a good average. The results was able to conlude that Quantum Teaching learning method based on the JAS approach to the character and conservation effective to activities and learning outcomes of student.Â Penelitian ini bertujuanÂ  mengukur efektivitas pembelajaran dengan metode Quantum Teaching pada pendekatan Jelajah Alam Sekitar berbasis karakter dan konservasi terhadap aktivitas dan hasil belajar serta karakter siswa di SMP N 1 Bae Kudus. Pembelajaran dikatakan efektif apabila secara klasikal minimal 80% siswa mencapai KKM dan keaktifan siswa menunjukkan â¥ 75% aktif serta respon karakter sikap siswa baik. Jenis penelitian adalah penelitian quasi eksperimental menggunakan desain Control group pretest-posttest. Sampel penelitian adalah kelas VII F dan VII G yang ditentukan secara purposive random sampling. Variabel bebas meliputi penerapan Metode Quantum Teaching pada pendekatan JAS berbasis karakter dan konservasi, sedangkan variabel terikatnya adalah aktivitas dan hasil belajar siswa. Pengujian menggunakan uji t menunjukkan selisih pretest-posttest kelas eksperimen lebih besar dari kelas kontrol. Hasil analisis uji n-gain aktivitas belajar siswa kelas eksperimen diperoleh rerata klasikal yang lebih tinggi daripada kelas kontrol. Analisis karakter siswa yang diukur dengan skala sikap diperoleh rata-rata baik. Hasil penelitian menunjukkan bahwa pembelajaran dengan metode Quantum Teaching pada pendekatan JAS berbasis karakter dan konservasi efektif diterapkan untuk meningkatkan aktivitas dan hasil belajar siswa.